2016
DOI: 10.1111/jbi.12842
|View full text |Cite
|
Sign up to set email alerts
|

Geographical clines of body size in terrestrial amphibians: water conservation hypothesis revisited

Abstract: Aim Faced with the dispute regarding spatial gradients of body size in ectotherms, we build upon their long‐known allometric relationship with water economy, which scales with thermal and hydric regimes, to revisit and refine the water conservation hypothesis (WCH). We provide a brief description of the WCH, including its physiological basis and geographical predictions for body size clines in terrestrial amphibians, and test it against heat‐based hypotheses in four amphibian clades. Location The Americas. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 58 publications
(127 reference statements)
3
82
0
Order By: Relevance
“…Several studies have shown that moisture can be more correlated with intraspecific variation in body size of animals than temperature, and anurans usually follow this trend (McDiarmid 1968;Nevo 1972Nevo , 1973Yom-Tov & Geffen 2006;Castellano & Giacoma 1998;Olalla-T arraga et al 2009;Gouveia & Correia 2016;Oromi et al 2012;Oyamaguchi et al 2016; this study). Among anurans, it is expected that because they need to keep their skin moist in order to breath a simple mechanism to achieve this is decreasing the surface-to-volume ratio by increasing body size, a mechanism analogous to the conservation of heat.…”
Section: Body Size Variationmentioning
confidence: 53%
See 4 more Smart Citations
“…Several studies have shown that moisture can be more correlated with intraspecific variation in body size of animals than temperature, and anurans usually follow this trend (McDiarmid 1968;Nevo 1972Nevo , 1973Yom-Tov & Geffen 2006;Castellano & Giacoma 1998;Olalla-T arraga et al 2009;Gouveia & Correia 2016;Oromi et al 2012;Oyamaguchi et al 2016; this study). Among anurans, it is expected that because they need to keep their skin moist in order to breath a simple mechanism to achieve this is decreasing the surface-to-volume ratio by increasing body size, a mechanism analogous to the conservation of heat.…”
Section: Body Size Variationmentioning
confidence: 53%
“…BIO1 = Annual Mean Temperature, BIO4 = Temperature Seasonality (standard deviation 9 100), BIO12 = Annual Precipitation, BIO15 = Precipitation Seasonality (Coefficient of Variation). In addition, potential evapotranspiration (PET) for each point was obtained from CGIAR-CSI Global Soil-Water Balance Database (Trabucco & Zomer 2010) following Gouveia and Correia (2016) and Normalized Difference Vegetation Index (NDVI) of each site using images from 2000 (satellite Terra, MODIS sensor) with a spatial resolution of 1 km (https:// reverb.echo.nasa.gov/reverb/#utf8=%E2%9C%93&spatial_ map=satellite&spatial_type=rectangle). The NDVI provides values that are highly correlated with photosynthetic mass and primary productivity.…”
Section: Geographic and Environmental Variablesmentioning
confidence: 99%
See 3 more Smart Citations